Correlation Between Disaster Knowledge and Community Preparedness Toward Floods in Sungai Kakap Villange - Andini, Disty; Anasi, Putri Tipa; Christanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2025)
This study aims to describe whether or not there is a correlation between the level of disaster knowledge and preparedness in facing flood disasters among the community of Sungai Kakap Village, Sungai Kakap Sub-district. The method used is a descriptive quantitative method with a correlational research design using a cross-sectional approach. The population of this study consisted of 11,303 people, with a total sample of 100 respondents. Data collection techniques in this study were indirect communication techniques and documentary studies. The data collection instruments used were observation, questionnaires, and public documents. The results of the study showed that the level of disaster knowledge of the community in Sungai Kakap Village, Sungai Kakap Sub-district regarding flood disasters was 73.56%, which falls into the category of “Fairly Good.” Meanwhile, preparedness in facing flood disasters among the community of Sungai Kakap Village, Sungai Kakap Sub-district was 69.90%, also categorized as “Fairly Good.” Based on statistical calculations using the Product Moment correlation formula to measure the correlation between the level of disaster knowledge and preparedness in facing flood disasters, the results showed r count = 0.689 compared to r table = 0.195 at a significance level of 5%. Based on these findings, it can be concluded that r count ≥ r table at a 5% significance level, which means that there is a correlation between the level of disaster knowledge and preparedness in facing flood disasters among the community of Sungai Kakap Village, Sungai Kakap Sub-district. Thus, Ha is accepted and Ho is rejected.